Textile Based Sensing System for Lower Limb Motion Monitoring - (:unkn) unknown (SPRINGER INTERNATIONAL PUBLISHING AG, 2019)
In recent years, as a result of multidisciplinary studies in textile science and technology, sensor characteristics are added to the textile products. Thanks to the many features of e-textile products, motion monitoring can be done in novel ways. The prototype developed in this paper, is low-cost, low-power, easy-to-integrate, and fully capable of communicating with mobile devices in a wireless manner. The proposed sensor system can be used to monitor the healing process of patients with neurological injuries.